Power Imbalances in Collective Decision-Making: The Study of Minimum Wage Setting Cases - Elisa Susanti; Heru Nurasa; Ida Widianingsih (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2019)
This paper aimed to empirically describe the power imbalances issues in setting the minimum wage in Bandung Regency and West Bandung Regency. Formally, Regional Wage Council has been established based on equality. However, several power imbalances have occurred within it. This paper also aimed to figure out the way to balance the power in collective decision making in the case of minimum wage setting. Furthermore, the research method used in this research was based on qualitative approach. Also, informants in this research were members of Regional Wage Council, employers in the industrial sector, and trade unions/labor unions in Bandung Regency and West Bandung Regency. The results of this study showed that power imbalances empirically existed in the setting of minimum wage. These imbalances were due to the issues of representatives, the number of members, information resources, and uncertainty. Moreover, power imbalances in the setting of minimum wage have led to the government’s more dominant role. Under these conditions, the effort required to overcome the problem of imbalance is by increasing trust in the government and the commitment of each party to the rules and collective agreements.